Treatment with Quinoline-3-carboxamide does not successfully prevent immune-mediated glomerulonephritis in mice - Juliana Draibe; Ruth J. Pepper; Alan D. Salama (Nefrología (English Edition), 2016)
Introduction: Quinoline-3-carboximide compounds, such as paquinimod, which targets the protein S100A9, have demonstrated efficacy in treating autoimmune diseases. S100A9, in association with S100A8, forms the heterodimer S100A8/S100A9, known as calprotectin; that has been shown to be upregulated in numerous inflammatory disorders. We had previously demonstrated protection from glomerular disease in S100A9-deficient mice. The aim of this study was to assess the efficacy of paquinimod in the prevention and treatment of experimental glomerulonephritis. Methods: Nephrotoxic nephritis (NTN) was induced in C57BL/6 mice according to our standard protocol. Mice were treated with different doses of paquinimod either at disease induction (prevention group) or two days following induction (therapeutic group) and sacrificed 8 days following induction. Disease was assessed histologically (number of glomerular crescents, degree of glomerular thrombosis, number of infiltrating leucocytes and calprotectin expression) and biochemically (serum creatinine and urea levels, and urinary levels of protein). Results: Neither treatment with low (0.5 mg/kg) or high (25 mg/kg) doses of paquinimod, given preventatively or therapeutically, led to disease attenuation, as assessed by biochemical or histological parameters. Additionally, we found trends for an increase in renal glomerular calprotectin expression in the high dose groups, suggesting a possible feedback regulation of calprotectin expression. Conclusions: Our results show that paquinimod does not successfully prevent or treat mice with NTN. Other models of immune-mediated glomerulonephritis need to be tested to investigate the therapeutic potential of this compound in renal disease.